Analysis of electrical properties in lateral Schottky barrier diode based on n-GaN and AlGaN/GaN heterostructure - Liu, Honghui; Liang, Zhiwen; Wang, Fengge; Xu, Yanyan; Yang, Xien; Liang, Yisheng; Li, Xin; Lin, Lizhang; Wu, Zhisheng; Liu, Yang; Zhang, Baijun (Frontiers in Physics, 2022)
In this paper, the lateral Schottky barrier diodes (SBDs) with small capacitance and low turn-on voltage (Von) were fabricated on n-GaN and AlGaN/GaN heterostructure. The capacitances of lateral n-GaN SBD and lateral AlGaN/GaN SBD are 1.35 pF/mm and 0.70 pF/mm, respectively. Compared with the planar SBDs, the capacitances of lateral SBDs are reduced by about two orders of magnitude without sacrificing the performance of on-resistance (Ron) and reverse leakage current. For the planar and lateral n-GaN SBDs, the value of the Von is similar. However, compared with the planar AlGaN/GaN SBD, the Von of lateral AlGaN/GaN SBD is reduced from 1.64 V to 0.87 V owing to the anode metal directly contacting the two-dimensional electron gas. According to temperature-dependent I-V results, the barrier inhomogeneity of the lateral SBD is more intensive than the planar SBD, which is attributed to etching damage. The withstand voltage of SBD is a very important parameter for power electronic applications. Compared with the breakdown voltage of 73 V in the lateral n-GaN SBD, the lateral AlGaN/GaN SBDs exhibit a breakdown voltage of 2322 V. In addition, we found that Schottky contact introduces anode resistance (RA) by analysing the Ron distribution of lateral SBDs. The experimental results also show that the RA of lateral n-GaN SBD and lateral AlGaN/GaN SBD are 10.5 Ω·mm and 9.2 Ω·mm respectively, which are much larger than the ohmic contact resistance due to worsening anode contact by metal-induced gap states.